PELATIHAN MODEL FLIPPED CLASSROOM DAN MEDIA PEMBELAJARAN INOVATIF DALAM MENUNJANG PEMBELAJARAN BERDIFERENSIASI UNTUK GURU DI SMAN 4 TASIKMALAYA - Ningsih, Mega Prani; Novitasari, Nastiti; Ramadhan, Ilham Rohman; Herawati, Linda; Nurdianti, Raden Roro Suci (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Differentiated learning in the independent curriculum has an important role in ensuring that every learner gets a learning experience that is appropriate for their respective needs, interests and potentials. SMAN 4 Tasikmalaya is one of the high schools that have implemented the Independent Curriculum and conduct learning differentiated. However, teachers encountered limitations in utilizing the and learning media that can support differentiated learning. This is because every In the period of capacity building, teachers have not found suitable facilitators from the scope of higher level than school institutions. The condition the partners is the reason for the implementation team to offer solutions in the form of training for teachers regarding the application of learning models flipped classroom and innovative media to support differentiated learning at SMAN 4 Tasikmalaya. The training method consists of 9 stages, including: 1) Preparation; 2) Coordination Meeting of the Service Implementation Team; 3) Coordination Meeting with the Principal and the training activity committee team; 4) Implementation Preparation; 5) Implementation of service; 6) making progress reports; 7) mentoring; 8) program evaluation, 9) preparation of final reports and service outputs. Throught this activity, teachers have the opportunity to improve skills, especially in Implementing interactive learning models and media.